Changes in the gastrointestinal tract structures, oxygen consumption and growth of Ephinephelus coioides larvae under different feeding regimes - Primavera-Tirol, Yasmin H. (Miagao, Iloilo University of the Philippines in the Visayas, 2015)
The general objective of this dissertation was to describe the changes in the gastrointestinal tract, oxygen consumption and growth Epinephelus coioides under different feeding regimes during critical periods in larval ontogeny. Newly-hatched E. coioides had a straight undifferentiated gut with the mouth and anus closed. On day 3, the mouth and anus were open and mucus cells were observed coinciding with the start of exogenous feeding. The GIT had differentiated into the buccopharyngeal cavity, esophagus, primordial stomach, intestine, and rectum. The incipient esophageal and pyloric shincter and the intestinal-rectal valve allowed the controlled release of partly digested food through the GIT extending the time for digestion and absortion of nutrients. lipid droplets were also observed in the anterior intestine denoting lipid metabolism in the enterocytes at this stage. The yolk and oil globule were completely exhausted on day 4 or the PNR. Mucosal folds and coiling of the GIT development. Other biological markers showing starvation were noted in unfed day 3 and day 4 larvae such as thinning of the mucosal layer, apoptotic enterocytes and a swollen gall-bladder. Cellular markers of starvation were also observed with reduced enterocyte heights further degraded on the PNR, when all the entrocyctes were in advanced stages of apoptosis. among day 3 fed larvae, entecytes of those fed artificial diet did not appear to have better nutritional condition than those fed natural food only with no significant difference in their heights. Dietary phospholipid deficiency was indicated in larvae co-fed artificial diet on diet 3 with an usually large chylomicron opening into the inter-enterocycte space, and on days 6 and 33 by intestinal steatosis. on day 6, macromolecular protein pinocytosis was noted in the hinggut with the observed supranuclear vacuoles coincident with exogenous feeding of the larvae. On day 19, markers for the onset of metamorphosis were observed such as pharyngeal teeth, taste buds, gastric glands, and pyloric caeca were observed as well as secondary branching of the anterior and posterior intestine. Scant to absent lipid droplets in the enterocyctes of larvae disclosed geightened nutritional requirement preparatory to metamorphosis. On day 33, the GIT was more developed with many mucus and goblet cells, and better immunity fitness with eosinophilic granule cells (EGCs) observed in the intestinal epithelia. Growth depensation was noted in larvae fed solely natural food and co-fed artificial diet. Cannibalism as a cause of mortality was validated among larvae fed solely natural food on day 33 by the computed maximum larval sizes well-above the 30% threshold size difference characteristic of cannibals. Based on the foregoing observations, it may be more advantageous to start supplementing the natural food with artificial diet starting around day 15 when nutritional requirement may be increased in preparatio for the transformation processes in metamorphosis. Future studies on grouper larval nutrition may consider the appropriate dietary phospholipid levels and larval competence to biosynthesize highly-unsaturated fatty acid (HUFA) from linoliec acid vis-a-vis the use of plant ingredient in artificial diet formulations. In vivo challenge tests may validate appropriate dietary nutrient supplementation and lead to better feed formulation matching the varying energetic demands and digestive capacities of developing E. coiides at different larval stages.
Dissertation (Doctor of Philosophy in Fisheries-Aquaculture) -- Miagao, Iloilo : University of the Philippines in the Visayas, January 2015.
Keywords: Epinephelus coioides